Simile demonstratives in Croatian : quantity, quality and beyond - Brala Vukanović, Maja (Array, 2021)
We investigate a particular subclass of semantic features associated with demonstratives of quantity and quality, and the respective interrogatives. We explore these lexical elements as they behave linguistically in simile constructions in Croatian. We show that the semantic features that can be focused on in similes are the same as the references of the full system of Croatian demonstratives. However, the possibility to focus on a particular semantic feature by a specific choice of demonstrative or interrogative in simile constructions is being replaced in usage by the generic simile word "kao".